#TITLE_ALTERNATIVE# - CHRISNA PURNAMA (NIM : 12012020), MARIO
Coastal area of Serdang Bedagai with 98º54’0.00” - 99º24’0.00” longitude dan 3º24’0.00” - 3º54’0.00” latitude is area of active sedimentation. It can be seen through wide deposition area at the site. The sediments are generally unconsolidated and in saturated condition, therefore, liquefaction analysis needs to be done. Liquefaction occurs by triggering condition that make sediments loose their effective stress and replaced by porewater pressure. Liquefaction hazard analysis in this research is using SPT data at research area, including susceptibility rating and its initiating factor. Various methods of liquefaction analysis are used for determining factor safety of liquefaction (FSL) based on sediment characteristics. Based on analysis, research area has 3 sediment types, they are: marsh clay sediment, beach sand sediment, and beach silt sediment. Coastal area of Serdang Bedagai possess moderate to high susceptibility with SRF (Susceptibility Ration Factor) value of 20.25 – 27.00. Liquefaction is more likely to occur in non-plastic layer of sediment. Ratio of CRR (Cyclic Resistance Ratio) to CSR (Cyclic Stress Ratio) of earthquake with Mw = 7.0 to Mw = 9.0 show that research area has liquefaction risk because it has SF (Safety Factor) less than 1 (one).